Facile Fabrication of Starch‐Based UV Barrier Films with Remolding Ability and Reinforcement for Water Resistance - Kazuki Shibasaki; Yu‐I Hsu; Hiroshi Uyama (Macromolecular Materials and Engineering)
Abstract Petroleum‐derived plastics are harmful to ecosystems because they are not decomposed in the natural environment. Therefore, the replacement of petroleum‐derived plastics with biodegradable plastics has attracted considerable attention. UV‐barrier films in the agricultural and packaging fields are mainly composed of petroleum‐derived plastics, which have a negative impact on the ecosystem when they leak into the environment. Thermoplastic starch (TPS) is an inexpensive and sustainable biodegradable plastic that has recently attracted considerable attention. In this study, the addition of UV barrier properties and remolding ability to TPS for replacing petroleum‐derived UV barrier films are investigated. Also, a biodegradable polyester coating is studied to improve the water resistance of the prepared UV‐barrier TPS (U‐TPS). To prepare U‐TPS, a conjugated enamine structure is formed by reacting starch acetoacetate with diamine monomers during melt kneading. U‐TPS exhibits high UV barrier properties across the UV regions (200–400 nm) owing to the presence of acetoacetyl groups and enamines. These results indicate the possibility of increasing the utilization of TPS in agriculture and as a packaging material.